A survey of bdelloid rotifers from coastal ponds in Southern Norway - Giulia Lin; Michael Plewka; Erling Brekke; Øystein N. Kielland; Glenn Dunshea; Diego Fontaneto (Journal of Limnology)
We report the results of the first survey of bdelloid rotifers, microscopic aquatic animals, in continental Norway, collected from coastal ponds in the Southern part of the country in Autumn 2021, using a morphological approach in species identification. Out of 25 ponds, 19 bdelloid species were found, ten in water samples and another nine in limno-terrestrial habitats just above the waterline of the ponds. Seven of the species are new records for mainland Norway. Three species could be identified to genus level only and may be novel taxa, not only for Norway but for science: further studies are needed on these animals to clarify their taxonomic identity. We also obtained COI sequences from 194 animals of eight of the species to compare them with what is known in GenBank in a phylogenetic context and confirm the reliability of morphological identification. This data contributes to our understanding of the taxonomic and biogeographic diversity of bdelloid rotifers in Norway. In addition, the newly available sequences increase the coverage of the reference library of bdelloid rotifers for future studies employing DNA metabarcoding.